PEMANFAATAN TOOLS KNOWLEDGE MANAGEMENT SYSTEM PADA PEMBELAJARAN MULTIMEDIA INTERAKTIF “VIRTUAL DRIVE NETWORK” STUDI KASUS : SMA MUHAMMADIYAH 13 JAKARTA - Maisyaroh, Maisyaroh (LPPM Universitas Nusa Mandiri, 2016)
Knowledge management (KM) is a series of activities used by an organization to identify, create, describe, and distribute knowledge for reuse, is known and studied in the organization. The emergence of a new technology in the field of information and communication in the form of tools Knowledge Management System to multimedia learning, as a means of supporting learning systems and efforts to improve the quality of good learning process, so as to create high school that can produce graduate students of high school quality. School is where the process of transferring knowledge, both between teachers and students, students with students, and teachers with teachers. SMA 13 Jakarta Muhammadiyah has implemented the concept of Knowledge Management System by implementing interactive multimedia-based learning as a means of support systems in the process of learning and teaching for teachers. Through this research can know the extent to which the use of tools